2014
DOI: 10.3390/antiox3030502
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Major Antioxidant Compounds and Radical Scavenging Activity of Palm Oil and Rice Bran Oil during Deep-Frying

Abstract: Changes in antioxidant properties and degradation of bioactives in palm oil (PO) and rice bran oil (RBO) during deep-frying were investigated. The alpha (α)-tocopherol, gamma (γ)-tocotrienol and γ-oryzanol contents of the deep-fried oils were monitored using high performance liquid chromatography, and antioxidant activity was determined using 2-diphenyl-1-picryl hydrazyl (DPPH) radical scavenging activity. Results revealed that the antioxidant activity of PO decreased significantly (p < 0.05), while that of RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
2
13
0
2
Order By: Relevance
“…Results of numerical optimization suggested that maximum desirability (0.89) could be obtained by formulation of noodles at 24.61% sorghum, 13.23% soy and 2.95% gluten, respectively. At the optimal level, predicted values of responses such as cooking time, cooked weight, cooking loss, hardness and overall acceptability were 8 (min), 17.38 (g), 11.01 (g/100 g), 36.78 (N), 7.3, respectively. Model validity was also confirmed through performing the experiments at optimum levels of independent variables (24.61% sorghum, 13.23% soy and 2.95% gluten).…”
Section: Optimized Level Of Variables and Verification Of Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of numerical optimization suggested that maximum desirability (0.89) could be obtained by formulation of noodles at 24.61% sorghum, 13.23% soy and 2.95% gluten, respectively. At the optimal level, predicted values of responses such as cooking time, cooked weight, cooking loss, hardness and overall acceptability were 8 (min), 17.38 (g), 11.01 (g/100 g), 36.78 (N), 7.3, respectively. Model validity was also confirmed through performing the experiments at optimum levels of independent variables (24.61% sorghum, 13.23% soy and 2.95% gluten).…”
Section: Optimized Level Of Variables and Verification Of Modelmentioning
confidence: 99%
“…Total phenolic content of multigrain noodles was significantly (P \ 0.05) higher (84.57 ± 1.42 mg/100 g GAE and) than the control noodles (59.33 ± 2.18 mg/100 g GAE) and Maggie noodles (40.76 ± 0.82 mg/100 g GAE), possibly linked with the higher phenolic content of soy flour and sorghum flour used in multigrain formulation [13,35]. Antioxidant result showed that Maggie noodles had significantly (P \ 0.05) higher DPPH inhibition activity (37.98 ± 0.06%), compared with multigrain (19.64 ± 0.20%) and control noodles (17.20 ± 0.26%) that might be associated with the presence of natural antioxidants inside the vegetable oil utilized during processing and frying of the noodles [36]. Further, fortification of additives as antioxidant during manufacturing of Maggie noodles could also be the reason of highest antioxidant activity of Maggie noodles.…”
Section: Optimized Level Of Variables and Verification Of Modelmentioning
confidence: 99%
“…Since repeatedly fried oils lose their ability to scavenge free radicals, palm oil loses its antioxidant ability as its duration and frequency of frying increase. Antioxidants such as α -tocopherol and γ -tocotrienol within palm oil are degraded faster than those in other oils due to more oxidation of fatty acids [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Palm yağının yüksek oksidatif stabiliteye sahip olması ve dumanlanma noktasının nispeten yüksek olması özellikle kızartma yağı olarak kullanılmasına olanak sağlamaktadır. Ancak yapılan bir çalışmada, palm yağının kızartmada kullanılması ile antioksidan özelliğinin önemli düzeyde azaldığı bildirilmiştir (14). (Tablo 1)…”
Section: Palm Yağının Yapısı Ve öZellikleriunclassified